Comparative effectiveness of adjuvant treatment for hepatocellular carcinoma with high risk of recurrence: A systematic review and network meta-analysis - Zha Peng; Leigu Shen; Yaqiong Wang; Boyu Chen; Zhuangrong Zhu; Chengyi He; Hai Huang (PLoS ONE, 2025)
Objective To identify the most effective postoperative intervention regimen for persons with hepatocellular carcinoma (HCC) at high risk of recurrence. Methods A network meta-analysis was conducted by collecting eligible studies from Medline, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science databases. Pairwise and network meta-analyses were applied to pooled data on overall survival (OS) and recurrence-free survival (RFS). Results 35 studies involving 6,372 patients were analyzed. Pairwise meta-analysis showed higher OS (HR = 0.64, 95% CI: 0.56–0.72; P < 0.001; I 2 = 70.9%, random effects model) and RFS (HR = 0.62, 95%CI 0.56–0.70; P < 0.001; I 2 = 60.2%, random effects model) in the adjuvant intervention group compared to surgery alone. ICIs&TKIs (SUCRA = 87.3%) was significantly more effective for OS, and TKIs&TACE (SUCRA = 84.1%) was significantly more effective for RFS. Conclusions Reasonable postoperative intervention regimens can reduce recurrence risk and improve prognosis. ICIs&TKIs and TKIs&TACE are likely the two most effective adjuvant intervention regimens for individuals with HCC who are at high risk of recurrence.